Solve for x
x=0.25
Graph
Share
Copied to clipboard
\frac{9}{5}x+\frac{9}{5}\times \frac{7}{2}=\frac{129}{20}+1.2x
Use the distributive property to multiply \frac{9}{5} by x+\frac{7}{2}.
\frac{9}{5}x+\frac{9\times 7}{5\times 2}=\frac{129}{20}+1.2x
Multiply \frac{9}{5} times \frac{7}{2} by multiplying numerator times numerator and denominator times denominator.
\frac{9}{5}x+\frac{63}{10}=\frac{129}{20}+1.2x
Do the multiplications in the fraction \frac{9\times 7}{5\times 2}.
\frac{9}{5}x+\frac{63}{10}-1.2x=\frac{129}{20}
Subtract 1.2x from both sides.
\frac{3}{5}x+\frac{63}{10}=\frac{129}{20}
Combine \frac{9}{5}x and -1.2x to get \frac{3}{5}x.
\frac{3}{5}x=\frac{129}{20}-\frac{63}{10}
Subtract \frac{63}{10} from both sides.
\frac{3}{5}x=\frac{129}{20}-\frac{126}{20}
Least common multiple of 20 and 10 is 20. Convert \frac{129}{20} and \frac{63}{10} to fractions with denominator 20.
\frac{3}{5}x=\frac{129-126}{20}
Since \frac{129}{20} and \frac{126}{20} have the same denominator, subtract them by subtracting their numerators.
\frac{3}{5}x=\frac{3}{20}
Subtract 126 from 129 to get 3.
x=\frac{3}{20}\times \frac{5}{3}
Multiply both sides by \frac{5}{3}, the reciprocal of \frac{3}{5}.
x=\frac{3\times 5}{20\times 3}
Multiply \frac{3}{20} times \frac{5}{3} by multiplying numerator times numerator and denominator times denominator.
x=\frac{5}{20}
Cancel out 3 in both numerator and denominator.
x=\frac{1}{4}
Reduce the fraction \frac{5}{20} to lowest terms by extracting and canceling out 5.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}